Une situation préoccupante : les investissements canadiens au Brésil dans les années 70 et 80 - Holly, Daniel (Études internationales, 1992)
This article is about Canadian investments in Brazil in the 70's and the 80's. It attempts to explain the relative decline of Canada's position on the Brazilian market. Canada was the 3rd largest investor in Brazil in the 60's. By the middle of the 80's, it ranked 6th. This paper argues that this situation is mainly due to the insufficient development of R-D in Canada and the consequent low level of technological innovation in this country. One significant effect of that is the inability of Canadian enterprises to compete successfully with those of other countries. This is supported by the massive concentration of investments in Brazil by Canadian-owned firms in the more traditional industries (mining, smelting, etc.), the dominant position of Canadian-based affiliates of foreign firms in that process (Canadian investments in Brazil) and their concentration in the most technologically-advanced industries, the over-all technological dependence of the Canadian economy and the low level of funding of R-D activities.